Outcomes with multimodal therapy for elderly patients with rectal cancer. Issue 2 (10th December 2015) - Thiels, C. A.; Bergquist, J. R.; Meyers, A. J.; Johnson, C. L.; Behm, K. T.; Hayman, A. V.; Habermann, E. B.; Larson, D. W.; Mathis, K. L.
Abstract : Background: Treatment guidelines for stage II and III rectal cancer include neoadjuvant chemoradiotherapy, surgery and postoperative adjuvant chemotherapy. Although data support this recommendation in younger patients, it is unclear whether this benefit can be extrapolated to elderly patients (aged 75 years or older). Methods: This was a retrospective review of patients aged at least 75 years with stage II or III rectal cancer who underwent surgery with curative intent from 1996 to 2013 at the Mayo Clinic. Kaplan–Meier analysis and log rank test were used to compare overall survival between therapy groups. Cox proportional hazards model was used to estimate the independent effect of treatment group on survival. Results: A total of 160 elderly patients (median age 80 years) with stage II (66) and stage III (94) rectal cancer underwent surgical resection. Only 30·0 and 33·8 per cent received neoadjuvant or adjuvant therapy respectively. Among patients with stage II disease, there was no significant difference in 60‐month survival between patients who received any additional therapy and those who had surgery alone (55 versus 38 per cent respectively; P = 0·184), whereas additional therapy improved survival in patients with stage III tumours (58 versus 30 per cent respectively; P = 0·007). Multivariable analysis found a survival benefit for additional therapy in elderly patients with stage III disease (hazard ratio 0·58, 95 per cent c.i. 0·34 to 0·98). Conclusion: A multimodal approach in elderly patients with stage III rectal cancer improved oncological outcomes. Abstract : Treatment should not be determined by age alone